Pemanfaatan Buku Saku Dalam Kegiatan Pendidikan Kesehatan Terhadap Peningkatan Pengetahuan Personal Hygiene Saat Menghadapi Menstruasi - Simanjuntak, Herlina; Dede Mulyani; Diyan Annisa Putri (Akademi Kebidanan Bunga Husada Samarinda, 2025)
Lack of knowledge of personal hygiene for menstruation will cause various health problems related to reproductive organs. To avoid various reproductive health problems, health education is needed about knowledge of personal hygiene when menstruation with effective media. The purpose of this study was to determine the effect of health education with pocket book media on knowledge of personal hygiene when menstruation in female students of SMP Negeri 1 Cikarang Timur in 2024. This type of research was a quasi-experimental study with a one group pre-test-post-test design. The population in the study were all 132 female students in grade VII at SMP Negeri 1 Cikarang Timur. The sample used was 99 female students with a stratified random sampling technique. The data collection instrument used a questionnaire. Bivariate analysis used the Wilcoxon Test. The results of the study showed that there was an increase in knowledge of personal hygiene when menstruation after being given a pocket book in health education. The bivariate test obtained a significant p-value of 0.001. It can be concluded that there was an effect of health education with pocket book media on knowledge of personal hygiene when menstruation in female students of SMP Negeri 1 Cikarang Timur in 2024.